2007
DOI: 10.1007/s11705-007-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Advances in chemical synthesis and application of metal-metalloid amorphous alloy nanoparticulate catalysts

Abstract: This paper reviews the advances in the chemical synthesis and application of metal-metalloid amorphous alloy nanoparticles consisting of transition metal (M) and metalloid elements (B, P). After a brief introduction on the history of amorphous alloy catalysts, the paper focuses on the properties and characterization of amorphous alloy catalysts, and recent developments in the solution-phase synthesis of amorphous alloy nanoparticles. This paper further outlines the applications of amorphous alloys, with specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 125 publications
0
21
0
Order By: Relevance
“…Supported nickel nanoparticles have been reported frequently in magnetic science and catalysis science. In particular, nickel nanoparticles supported on metal oxides with unique chemical and physical properties have been widely used as catalysts for many hydrorelated reactions, such as the hydrogenation, hydrogenolysis, and hydrotreating reactions [1][2][3][4][5][6]. Such supported nickel nanoparticles are mostly synthesized by the impregnation/deposition of nickel complexes from an aqueous solution onto the supports [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supported nickel nanoparticles have been reported frequently in magnetic science and catalysis science. In particular, nickel nanoparticles supported on metal oxides with unique chemical and physical properties have been widely used as catalysts for many hydrorelated reactions, such as the hydrogenation, hydrogenolysis, and hydrotreating reactions [1][2][3][4][5][6]. Such supported nickel nanoparticles are mostly synthesized by the impregnation/deposition of nickel complexes from an aqueous solution onto the supports [4].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a new method for the synthesis of supported nickel nanoparticles with high dispersion as well as high nickel loading is significant for their further catalytic application. The electroless nickel-plating method should be a suitable choice because it has been proved to control the nickel loading, particle size, and dispersion of nickel nanoparticles [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, amorphous nanomaterials have attracted increasing interest because of their scientific importance and promising applications in optics, electronics, and catalysis. [8][9][10][11] For example, Lu et al found that pressure-induced amorphous Ta 2 O 5 nanowires show significant improvement in electrical conductivity. 12 In contrast to the corresponding crystalline nanoparticles of the same mean diameter, the amorphous Cu nanoparticles showed a low-energy shift of surface plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel boride nano-catalysts have gained increasing interest as novel catalytic materials in hydrogenation reactions [1]. The high concentration of coordinating unsaturated active sites in these amorphous alloy nano-particles donates them higher activity and selectivity with respect to their crystalline counterparts [2].…”
Section: Introductionmentioning
confidence: 99%